Efficacy of endometrial microbiota testing-guided personalized therapy in infertile women stratified by CD138 status: a retrospective cohort study - Fang He; E’Nuo Peng; Jiao Lin; Zhuo Mao; Xiaowei Lu; Hui Xu; Lei Guo; Yangyun Zou; Jing Wang; Sijia Lu; Xianghong Huang (Frontiers in Endocrinology, 2026)
Background Chronic endometritis (CE) is a persistent inflammatory condition of the endometrium associated with infertility. Current diagnosis relies on histopathological markers like CD138, which may not fully assess the functional state of the endometrial microenvironment. This study aimed to investigate whether the endometrial microbiome test (EMT) combined with personalized therapy could improve pregnancy outcomes in infertile women undergoing IVF, compared with standard management based on CD138 results. Methods This retrospective cohort study included 336 infertile women (aged 22–37 years) who underwent the CD138 test in Xiangtan Central Hospital between January 2020 and December 2022. Among them, 162 patients opted to undergo concurrent EMT using 16S rRNA sequencing and received EMT-guided personalized treatment. After excluding patients with missing CD138 results, those who underwent sequential embryo transfer, and those with endometrial thickness <7 mm at the time of transfer, 151 patients were included in the EMT group and 155 in the non-EMT group. The non-EMT group received standard management based on CD138 results (empirical antibiotics for CD138-positive patients; no treatment for CD138-negative patients). Clinical outcomes were compared between the two groups overall and after stratification by CD138 status. Multivariable logistic regression was performed to adjust for confounders. Results The overall live birth rate in the EMT group was 64.24% (97/151), which was higher than the non-EMT group (46.45%, 72/155, adjusted p=0.004). Among CD138-negative patients, EMT-guided therapy was associated with a significantly higher clinical pregnancy rate (70.89% vs. 53.41%, adjusted p=0.011), ongoing pregnancy rate (62.03% vs 46.59%, adjusted p=0.041), and live birth rate (60.76% vs. 43.18%, adjusted p=0.030) compared to no treatment. Among CD138-positive patients, EMT-guided therapy showed no significant improvement for the ongoing pregnancy rate (69.44% vs. 52.24%, adjusted p=0.142) or the live birth rate (68.06% vs. 50.75%, adjusted p=0.118) compared to empirical antibiotic treatment. Conclusion EMT-guided personalized therapy was associated with favorable reproductive outcomes in CD138-negative women with infertility, identifying a subgroup that may benefit from microbiota-targeted intervention. For CD138-positive patients, the added value of EMT over empirical antibiotic therapy remains uncertain and warrants further investigation. EMT may guide treatment in CD138-negative cases via sequential diagnosis, though prospective validation is needed.